Propensity for innovation in textile manufacturing companies at the city of Gaspar/SC, national capital of children's fashion - Hora, Givaldo Bezerra da (2024)
Objective: to analyze the propensity for innovation in textile manufacturing companies in the town of Gaspar/SC. Methodology: characterized as descriptive, the research uses a quantitative approach. An electronic questionnaire was administered, answered by 35 textile companies based in a Local Productive Arrangement (LPA). Results: the results highlight that, among the implemented innovation typologies, there is a domain of process innovation. Within the main factors that motivate innovation is the adoption of more efficient production methods. The predominant problems/challenges are a lack of qualified labor and the high costs of innovation. Theoretical/methodological contributions: to offer a systematic vision about the theme of innovation applied to a productive arrangement of national relevance. Relevance/Originality: the gathering of data and the discussion on innovation in textile manufacturing companies for children's clothing in a specific Brazilian productive arrangement were not previously done. Social/management contributions: The research provides to company managers of textile confections that their effort on the innovation process generates only incremental innovations, derived from external knowledge provided by suppliers, that generates a dependency to innovate.